ON DWELLING HEIDEGGERIAN ALLUSIONS TO ARCHITECTURAL PHENOMENOLOGY - EL-BIZRI, Nader (Studia Universitatis Babeș-Bolyai Philosophia, 2015)
This paper investigates the phenomenon of dwelling in Heidegger’s thought. This endeavour is undertaken in the context of accounting for his take on the gathering of the fourfold (earth, sky, mortals, and divinities) in things amongst which we dwell. It is also situated in relation to his existential analytic of Dasein, his reflections on death, time, and space. This line of inquiry is moreover placed within the broader constellation of the published recollections of Heidegger’s thought in connection with his meditations on the unfolding of the essence of modern technology and its en-framing, his contemplation of the origins of the work of art, and the way these aspects connect with his call for re-thinking dwelling anew in terms of what can be seen as an ontological response to the questions of the meaning, truth, and place of being.